PENYELESAIAN PERKARA PERDATA BERBASIS E-COURT PADA PENGADILAN NEGERI PADANG KELAS IA - Ameliza, Dwikornida dan (Normative Jurnal Ilmiah Hukum, 2024)
One of the instruments in the form of court services to the public in terms of online case registration is through the e-court application which is regulated in Supreme Court Regulation Number 3 of 2018 concerning Electronic Administration of Cases in Court through the e-court application. The E-Court application has been massively socialized to the public, but there are still many people, even lawyers, who are still reluctant to register their cases via the E-Court application on the grounds that it is troublesome and they don't really understand how the application works, so it seems difficult. In 2019 the Supreme Court again issued Supreme Court Regulation Number 1 of 2019 concerning Electronic Administration of Cases and Trials in Court as a replacement for Supreme Court Regulation Number 3 2018 concerning Electronic Administration of Cases in Court. This research is descriptive in nature using a sociological juridical approach. The data used in this research includes primary data and secondary data using primary, secondary and tertiary legal materials. The analysis used in this research is qualitative analytical. The results of the research are as follows: first, the implementation of e-court-based civil case settlement at the Class IA Padang District Court has been carried out in accordance with the rules. Second, the obstacles faced in resolving e-court-based civil cases at the Class IA Padang District Court are the summoning of the Defendant which is done by registered letter so that its validity is difficult to assess, the E-Court server often experiences errors and the parties' lack of understanding of the trial system. carried out electronically. Regarding the obstacles faced, it is hoped that the Supreme Court will improve the quality and capacity of the server to support the operation of the E-Court application, and provide legal education regarding electronic trials so that it is better known to the lay public.